Early outcomes after left subclavian artery revascularisation in association with thoracic endovascular aortic repair. (February 2017) - Oladokun, Dare; Patterson, Benjamin O; Brownrigg, Jack RW; deBruin, Jorg L; Holt, Peter J; Loftus, Ian; Thompson, Matthew M
Approximately 40–50% of patients undergoing thoracic endovascular aortic repair require left subclavian artery coverage for adequate proximal landing zone. Many of these patients undergo left subclavian artery revascularisation. However, outcomes data for left subclavian artery revascularisation in the context of thoracic endovascular aortic repair remain limited. In this study, 70 left subclavian artery revascularisation procedures, performed on thoracic endovascular aortic repair patients at a tertiary hospital, were retrospectively reviewed. Particular emphasis was placed on revascularisation-related outcomes during staging interval between revascularisation and thoracic endovascular aortic repair. Forty-six (66%) carotid-subclavian bypass, 17 (24%) carotid-carotid-subclavian bypass and 7 (10%) aorto-inominate-carotid-subclavian bypass procedures were performed. There were no strokes or mortalities following left subclavian artery revascularisation procedures alone. Three (10%) minor complications occurred including a seroma, a haematoma and a temporary neuropraxia. Separation of complications following left subclavian artery revascularisation from those of the associated thoracic endovascular aortic repair can be difficult. Early outcomes data from patients who underwent left subclavian artery revascularisation in isolation indicate that the procedure is safe with low complication rates.